Seed Priming and Priming Duration Influence on Growth and Yield of Wheat (Triticum aestivum L.) under Rainfed Condition of Hilly Uttarakhand - Panwar, Mayank Singh; Upadhyay, R. G.; Kumar, Ajay; Paliwal, Arunima (International Journal of Bio-resource and Stress Management, 2021)
Insufficient stand establishment of winter wheat is a major problem in the rainfed region of the Uttarakhand hills. In order to increase germination and early establishment in the field under rainfed condition of hilly tracts this study was conducted at college of forestry VCSG University of Horticulture and Forestry, Ranichauri, Tehri Garhwal, Uttarakhand, India. The ten treatments were laid out in randomized block design with three replications in field. The treatments were VL 892 primed for 12 hrs with normal water, VL 892 primed for 24 hrs with normal water, VL 892 primed for 12 hrs with lemon water, VL 892 primed for 24 hrs with lemon water, VL 829 primed for 12 hrs with normal water, VL 829 primed for 24 hrs with normal water, VL 829 primed for 12 hrs with lemon water, VL 829 primed for 24 hrs with lemon water, VL 892 with no priming, and VL 829 with no priming. Significantly higher grain Yield of wheat was recorded in VL 829 primed with normal water for 24 hours which was statistically on par with VL 829 primed for 12 hrs with normal water, VL 892 primed for 24 hrs with normal water and VL 892 primed for 12 hrs with normal water. Significantly higher grain yield was recorded in case of priming with normal water than the priming with lime water.